Effect of warfarin on survival in patients with concomitant left ventricular systolic dysfunction and pulmonary hypertension: a population cohort study. (27th November 2014) - Goudie, Andrew; Elder, Douglas; Deshmukh, Harshal; Szwejkowski, Benjamin R; Lang, Chim C; George, Jacob
<x xml:space="preserve">Abstract</x> Background The use of oral anticoagulation in patients with heart failure in sinus rhythm remains controversial as previous large randomized controlled trials (RCTs) have not shown a survival benefit. However, heterogeneity exists among heart failure patients and it is possible that high‐risk subgroups may benefit from anticoagulation (warfarin). We hypothesize that one such subgroup are patients with heart failure and pulmonary hypertension (PH), conditions associated with coagulation abnormalities. Methods We conducted a retrospective, population‐based, longitudinal cohort study in patients with left ventricular systolic dysfunction (LVSD) and PH [defined as a right ventricular systolic pressure (RVSP) >35 mmHg] identified from echocardiograms performed between January 1994 to May 2011. This data was linked using a unique patient‐specific identifier to community‐dispensed prescriptions, hospital admissions, and mortality data. For comparison, we included patients with LVSD and no PH. Results A total of 2619 subjects with LVSD and a measurable RVSP were identified (mean ± SD age of 73 ± 12 years); 1606 out of 2619 had PH and 1013 out of 2619 had no PH. The overall mean follow‐up period was 2.56 ± 3.0 years. In patients with LVSD and PH, the use of warfarin was associated with an improved survival [hazard ratio (HR) = 0.72 95% confidence interval (CI) 0.58–0.90, P = 0.0003], fewer non‐cardiovascular disease‐related deaths (HR = 0.65, 95%CI 0.49–0.87, P = 0.0033 and showed a trend towards reduced cardiovascular disease‐associated mortality (HR = 0.72, 95%CI 0.51–1.02). Warfarin did not improve survival in those with LVSD with no PH. Conclusions In patients with both LVSD and PH, the use of warfarin is associated with a 28% reduction in mortality. Further prospective trials are required to confirm our findings.